Assemblages of aquatic bugs (Insecta: Hemiptera) at Littoral Zones of three reservoirs in Sarawak - Faridah, Hashim (Universiti Malaysia Sarawak, 2017)
Aquatic bugs belong to Order Hemiptera, contains three suborders, namely the true water bugs (Nepomorpha), semi-aquatic bugs (Gerromorpha) and shore bugs (Leptopodomorpha). They are useful as biological control agents, and also ecologically important in the food chains. This study aims to determine assemblages of aquatic bugs at littoral zones of three reservoirs in Sarawak with different ages, namely Batang Ai (31 years), Bakun (6 years) and Murum (3 years). The specific objectives are to determine the diversity of aquatic bugs, and to investigate the process of colonization by the fauna in the newly impounded reservoirs. Physicochemical conditions including water temperature, dissolve oxygen, pH, turbidity, conductivity, nitrate and chloride. Results showed that Murum has the highest abundance of aquatic bugs with 297 individuals followed by Batang Ai, with 183 individuals, Bakun with 58 individuals and lower Murum with 10 individuals. The dominant taxa in the reservoirs are Rhagadotarsus kraepelini and Nychia sappho.